Using an Evidence-Informed Approach to Improve Students' Higher Order Thinking Skills - Mireille Desirée Hubers (MDPI AG, 2022)
This study aimed to determine why university students performed relatively low on a writing assignment. In phase 1, questionnaire and performance data were collected and analyzed. This evidence-informed approach revealed that students' relatively low performance was caused by their relatively underdeveloped higher order thinking skills. A six-step research-informed procedure was designed to assist students' development of these skills. In turn, questionnaire data, performance data and observational data were collected in phase 2 to determine the effectiveness of the design and the quality of the implementation. The results indicated that students improved their higher order thinking skills. Alternative explanations did not play a role; the designed procedure was implemented with high fidelity and positively rated by the students. This study can aid university teachers in designing course materials for the development of students' higher order thinking skills.